Analisis Perbandingan Metode ROC-WASPAS dan Entropy-WASPAS dalam Keputusan Pemberian Reward Kinerja Pegawai Hotel - Aldisa, Rima Tamara (Building of Informatics, Technology and Science (BITS), 2022)
Employees are human resources in government or companies whose quality and capacity must always be improved. Assessment of employee performance is very necessary, this aims to get an assessment of employee performance achievements and give awards to employees who have good performance. In order for the assessment of performance achievements to be more effective, a method is needed in generating decisions. In making a decision to present prizes, performance, needs, the best work that must meet criteria such as Work Results, Integrity, Discipline, Ethics and Creativity. In this study, a comparative analysis of the combination of Rank Order Centroid (ROC) and Weighted Aggregated Sum Product Assessment (WASPAS) methods was carried out as well as a combination of Entropy and WASPAS. The ROC and Entropy methods are used to generate weight values, while the WASPAS method is a ranking method that requires weights. The results showed that alternative A5 was the best alternative with the highest score with a value of 2.958 on the ROC-WASPAS method and a value of 2.968 on the Entropy-WASPAS method